“Sevgili Ölümüz”: Abdülhak Hâmid’in Ardından Halkevlerinde Düzenlenen Anma Törenleri ve Bir Ulusal Mit Yaratım Süreci - Eskin, Şerif (FSM Vakıf Üniversitesi, 2017)
Son dönem Osmanlı edebiyatının en velût kalemlerinden Abdülhak Hâmid Tarhan, Cumhuriyet Türkiyesi’nde de varlık gösterebilmiş ve bununla beraber dönemin muktedirleri tarafından sahiplenilmiş istisnai bir tarihsel şahsiyettir. Geride bıraktığı külliyat her ne kadar teknik açıdan Cumhuriyet elitlerinin idealleri ve kültürel dönüşüm tasarıları ile tezat oluşturacak derecede “Osmanlı” hüviyetinde olsa da çeşitli yorumlama ve tevil girişimleriyle onun edebî şahsiyeti, tasarlanmaya çalışılan modern-seküler ulusal kanona bir referans hâline getirilmeye çalışılmıştır. Ölümünün (1937) hemen ardından CHP Halkevleri çatısı altında şair için düzenlenen anma törenleri kapsamında oluşan gündem ve bu merasimlerin icra ediliş biçimleri ilgili bağlamda önemli veriler barındırmaktadır. Bu çalışmada, söz konusu anma törenlerinde sergilenen ritüeller, teatral sunumlar ve şair hakkında irad edilen nutuklardan hareketle Abdülhak Hâmid’in hangi dayanaklar çerçevesinde bir ulusal deha olarak yorumlanıp mitleştirilmeye çalışıldığı ele alınacaktır.

Abdulhak Hamid Tarhan was one of the most active writers of the late Ottoman period and his corpus can be evaluated as the ‘modern Ottoman’ one. Althought he continued to write in the Republican period, his style and standpoint reflects an Ottoman taste that was not fit well to the Republican elits’ aims to redress the literary genres according to their new ideals. Nevertheless after his death in 1937, Hamid’s personality, but not much his corpus, was used to create a new national(ist) memory and space around his name as was the case to the most of the literary personas. In these attempts, as a ruling and only party of the period, People’s Houses hold ceremonies to commemorate Hamid. Strangely enough these commemorations didn’t aim to respect an important writer’s corpus, but to the contrary, to perform rituals that were very convenient to the ruling elits’ aspirations to create a new, secular and modern national memory and space. This article deals with these ceremonies, rituals and commemorations held in the name of Hamid in all part of Turkey in order to show that these must be seen as a way of trying to a national myth around the Republican regime.
“Our Beloved Dead”: The Commemorative Ceremonies Held in People’s Houses in Memory of Abdulhak Hâmid Tarhan and The Process of Creating a National Myth
Keywords: Abdülhak Hâmid Tarhan; Halkevleri; Anma törenleri; Edebiyat kanonu; Abdulhak Hâmid Tarhan; People’s Houses; Commemorative ceremonies; Literary canon